Ultrasound versus magnetic resonance imaging for calculating total kidney volume in patients with ADPKD: a real‑world data analysis - Fernandez, Juan M.; Hernández‑Socorro, Carmen Rosa; Robador, Lucas Omar; Rodríguez‑Esparragón, Francisco; Medina‑García, Daniela; Quevedo‑Reina, Juan Carlos; Lorenzo‑Medina, Mercedes; Oliva‑Dámaso, Elena; Pérez‑Borges, Patricia; Rodríguez‑Perez, José C. (The Ultrasound Journal, 2025)
Background and objectives: This study aimed to compare Total kidney volume (TKV) measurements using US-ellipsoid (US-EL) and MRI-ellipsoid (MRI-EL) in patients with autosomal-dominant-polycystic-kidney-disease (ADPKD). It also evaluated whether the agreement between right (RKV) and left (LKV) kidney volume measurements differed. Methods: Retrospective analysis of a prospective data-base that included consecutive patients diagnosed with ADPKD. Total kidney volumes by 3D-US-EL were compared with those by MRI-EL. Bland–Altman-plots, Passing–Bablok-regression, and the concordance-correlation-coefficient (CCC) were used to compare right (RKV), left (LKV), and TKV measurements. Results: Thirty-two ADPKD patients, 14(43.7%) women, were included. Mean measured (mGFR) and estimated (eGFR) glomerular-filtration-rate (GFR) were 86.5 ± 23.9 mL/min and 78.9 ± 23.6 mL/min, respectively. Compared with MRI-EL, TKV (Mean difference: − 85.9 ± 825.6 mL; 95%CI − 498.5 to 326.7 mL; p = 0.6787), RKV (Mean difference: − 58.5 ± 507.7 mL; 95%CI − 312.2 to 195.2 mL; p = 0.6466), and LKV (Mean difference: − 27.4 ± 413.5 mL; 95%CI − 234.1 to 179.2 mL; p = 0.7918) were lower with US-EL than with MRI-EL, although without significant differences. According to Passing and Bablok-regression analysis, the Spearman correlation-coefficient was 0.96 (95%CI 0.92 to 0.98); 0.91 (95%CI 0.82 to 0.96), and 0.94 (95%CI 0.87 to 0.97) in the RKV, LKV, and TKV, respectively; p < 0.0001 each, respectively. CCC of RKV, LKV, and TKV measurements were 0.95, 0.89, and 0.94, respectively. The mGFR and eGFR showed statistically significant negative correlations with TKV measured by both MRI-EL (p = 0.0281 and p = 0.0054, respectively) and US-EL (p = p = 0.0332 and p = 0.0040, respectively). Conclusions: This study found that ultrasound-based ellipsoid kidney volume measurements strongly correlated with MRI-based measurements, suggesting that ultrasound is a reliable, accessible alternative for assessing kidney volume, particularly when MRI is unavailable.